Answer:
x = 1 ,y = -2
Explanation:
Solve the following system:
{-4 y - 3 x = 5 | (equation 1)
3 y - 2 x = -8 | (equation 2)
Subtract 2/3 × (equation 1) from equation 2:
{-(3 x) - 4 y = 5 | (equation 1)
0 x+(17 y)/3 = -34/3 | (equation 2)
Multiply equation 2 by 3/17:
{-(3 x) - 4 y = 5 | (equation 1)
0 x+y = -2 | (equation 2)
Add 4 × (equation 2) to equation 1:
{-(3 x)+0 y = -3 | (equation 1)
0 x+y = -2 | (equation 2)
Divide equation 1 by -3:
{x+0 y = 1 | (equation 1)
0 x+y = -2 | (equation 2)
Collect results:
Answer: {x = 1 ,y = -2